Menyibak Penerapan PSAK 102 Atas Prosedur Akad Murabahah - Zezi Nanda Oktafiya; Chaidir Iswanaji (JAS (Jurnal Akuntansi Syariah), 2020)
This study aims to determine how the procedure or implementation of the murabahah financing contract at KSPPS BMT ARMA is it in accordance with PSAK 102 concerning murabahah or not. This research explains how the murabahah financing contract in KSPPS BMT ARMA. This study also discusses PSAK 102 regarding murabahah. The method used in this research is descriptive qualitative. This research was conducted at KSPPS BMT ARMA Magelang. In collecting data, the author uses several methods including observation is a method of direct observation carried out by researchers and interview methods. The results of the study can be seen that the accounting treatment of murabahah financing carried out at BMT ARMA is in accordance with accounting principles, namely PSAK 102.